Fridge studies – Rummage through the fridge to understand food waste. (1st October 2021) - Heidenstrøm, Nina; Hebrok, Marie
Abstract: Household food waste is a significant environmental challenge, and almost half of the total global food waste comes from households. Thus, it is crucial to understand why food is wasted at home. This paper proposes a new method, Fridge Studies, that provides knowledge on food waste drivers adding to the research currently documenting the amounts and types of food wasted. Fridge studies is based on social practice theory, suggesting that waste is produced through food handling practices . By rummaging through the fridge together with the study participants, this method provides thick descriptions of practices that generate food waste in an efficient manner. Researchers and participants talk while rummaging, selecting food items and telling their story, as well as photographing the fridge and its content. The method was developed as part of three projects on sustainable food consumption in Norway and has been employed in 57 households.